2023
DOI: 10.1186/s13019-023-02118-3
|View full text |Cite
|
Sign up to set email alerts
|

Early and mid-term outcomes after aortic valve intervention in patients with previous stentless or stented bioprostheses

Abstract: Background Limited data are available concerning comparative outcomes of redo aortic valve interventions, including surgery after aortic valve replacement (AVR) with either stented or stentless bioprostheses. We investigated the comparative outcomes of redo aortic valve interventions, including surgery after AVR with either stented or stentless bioprostheses. Methods The cohort consisted of 112 patients who underwent aortic valve intervention for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…When considering reintervening on a diseased prosthetic aortic valve, options include redo-surgical aortic valve replacement (SAVR) or valvein-valve (ViV) transcatheter aortic valve replacement (TAVR). Several studies over the past 10 years have demonstrated favourable outcomes with each of these strategies (1)(2)(3)(4)(5). Generally, it is believed TAVR offers a minimally-invasive low risk procedure, but with limited durability, whereas redo-SAVR is associated with higher risk, but greater durability.…”
Section: Introductionmentioning
confidence: 99%
“…When considering reintervening on a diseased prosthetic aortic valve, options include redo-surgical aortic valve replacement (SAVR) or valvein-valve (ViV) transcatheter aortic valve replacement (TAVR). Several studies over the past 10 years have demonstrated favourable outcomes with each of these strategies (1)(2)(3)(4)(5). Generally, it is believed TAVR offers a minimally-invasive low risk procedure, but with limited durability, whereas redo-SAVR is associated with higher risk, but greater durability.…”
Section: Introductionmentioning
confidence: 99%